Prevalence of Escherichia coli in the Community Acquired Bacteremic UTI in Southeast Asian Countries: A Mini-Review - Rosero, Joseph Angelo B.; Alvarez, Joanna Marie G.; Soriano, Hanniel Joy B.; Raymundo, Jennie Rose D.; Batisla-on, Catherine Joy E.; Morales, Kyla O.; Lirio, Mary Rose F. (Asian Journal of Biological and Life Sciences)
Urinary tract infection due to E. coli is common among Southeast Asian countries. However, there is limited research available providing the prevalence of E. coli in Urinary Tract Infection in Southeast Asia. With 94%, Myanmar, among the other Southeast Asian Countries had the highest prevalence rate of E. coli that causes Urinary Tract Infection. Brunei, on the other hand, had the lowest prevalence rate of 1.18%. Further, Vietnam accounts for more than 48% of the E. coli isolates in different SEA. Meanwhile, there is no data available at Timor-Leste making it difficult to know the prevalence of E. coli in the country. Despite having the most number of E. coli isolate among other region, there’s still limited data among Southeast Asian countries that could mean: (1) researchers had little interest in this filed, or (2) clinicians and researchers would still not acknowledge its high prevalence rate. Despite the limited data, clinician and researchers should be encouraged more to conduct study about the said topic to further widen the knowledge and to create permanent solutions to halt the infection brought by E. coli. Further, it is also highly suggested to create an organization that would monitor the prevalence of E. coli in different countries in Southeast Asia as this may be beneficial in order to prevent other severe cases of infections.
Keywords: Bacteremic Urinary Tract Infection; Community-acquired; Escherichia coli or E. coli; Southeast Asia; Urinary Tract Infection or UTI